THE EFFECT OF SERVICE QUALITY ON CONSUMER LOYALTY OF MIE GACOAN MEDAN PANCING - Meiriza, Mica Siar; Sitanggang, Rexsy Mardohot; Tambunan, Rahel Marito; Situmorang, Ninda Rohani; Manalu, Lija Tanjung; Pratiwi, Dian Maulina (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study explores and analyzes the influence of service quality on consumer loyalty at the semi-fast food restaurant, Mie Gacoan Medan Pancing. Using a quantitative approach, this study relied on primary data collected through a questionnaire from 100 respondents. The questionnaire was distributed both directly at the restaurant location and online through the WhatsApp platform, with a Likert scale of 1–5 to measure respondents' perceptions of service quality and consumer loyalty. Data analysis was carried out with the help of SPSS version 27 software, including validity and reliability tests to ensure instrument quality, normality tests to test data distribution, and simple linear regression to evaluate the influence of service quality on consumer loyalty. The study also conducted a determination test (R²) to assess the contribution of the independent variables to the dependent variable. The results showed that service quality had a positive and significant influence on consumer loyalty, with a significance value of 0.001. Service quality accounted for 58.4% of the variation in consumer loyalty. This research makes an important contribution to the development of service improvement strategies in the semi-fast food restaurant sector, particularly for Mie Gacoan managers. Additionally, the findings of this study are expected to enrich the literature related to service quality management and consumer loyalty in the culinary industry, especially in the local context. These results open up opportunities for further research to explore other variables that may also affect consumer loyalty in the industry.